Rivières du futur, wild rivers ? - Régis Barraud (VertigO)
Since the mid 1990s, new principles of ecological river management have been adopted on an international scale. In order to improve water quality and the aquatic environment, it is not sufficient to reduce pollution; it is also necessary to act on the very structure of rivers, such as to restore the physical processes that govern river dynamics. Amongst the most symbolic actions undertaken under this new river management paradigm is dam removal. Not only environmental associations, but also by institutional actors, increasingly put forward this solution. The removal of hydraulic works is accompanied by a physical and symbolical “liberation” of the river. The advocacy of dam removal of dams seems to be associated with the quest for a model of a wild river. This article proposes an analysis of the international movement of dam removal through a comparative study of its application and its socio-spatial implications in North America (origin of the movement) and Europe.